(untitled) (Journal of the College of Basic Education, 2022)
One of the important affects on the properties of composites is the adhesion strength at interface between the fiber and the matrix where could have a significant effect on crack propagation in the composites. The aim of this paper was to find that if the twisted bundle of glass fibers effected on the adhesion strength, i.e. the interfacial shear stress and the strain energy at interface of fiber reinforced polymer matrix composites, using, first, the interfacial shear stress by Cox model [1], second the energy release rate model derived by Nairn [2,3,4] which included the residual stress and friction effects as a theoretical analysis. The experimental part we used the microbond drag-out test [5] as tensile test. It was found when the turns numbers of glass fiber bundle of diameter (200 µm) about fiber axis increased the full debond force increased, so the interfacial shear stress and the energy release rate (strain energy) increased. Because the restrained of crack propagation increased as the screw thread pitch increased. The friction region in force-displacement curves for glass fiber bundle where the fiber twisted or not, was slip hardening and increased as twist number increased.